The Economic Implications of Psychosocial Peer Support for Health Workers in German Hospitals - Strametz R; Roesner H; Neusius T; Wiesenhuetter I; Bushuven S; Mira JJ; Hinzmann D; Heininger S (Journal of Healthcare Leadership)
Reinhard Strametz,1,* Hannah Roesner,1,2,* Thomas Neusius,1,* Isabell Wiesenhuetter,1 Stefan Bushuven,3,4 José Joaquín Mira,2,5 Dominik Hinzmann,6 Susanne Heininger7 1Wiesbaden Institute for Healthcare Economics and Patient Safety, RheinMain UAS, Wiesbaden, Germany; 2Miguel Hernández University of Elche, Elche, Spain; 3Training Center for Emergency Medicine (NOTIS e.V), Engen, 78234, Germany; 4Department of Anesthesiology and Critical Care, Medical Center - University of Freiburg, Faculty of Medicine, University of Freiburg, Freiburg, 79106, Germany; 5Fundación para el Fomento de la Investigación Sanitaria y Biomédica de la Comunitat Valenciana (FISABIO), Alicante, Spain; 6Department Clinical Medicine, Department of Anesthesiology and Intensive Care, TUM School of Medicine and Health, Technical University of Munich, Munich, Germany; 7Faculty for Applied Healthcare Sciences, Deggendorf Institute of Technology, Deggendorf, Germany*These authors contributed equally to this workCorrespondence: Reinhard Strametz, Wiesbaden Institute for Healthcare Economics and Patient Safety, RheinMain UAS, Bleichstr. 3, Wiesbaden, 65183, Germany, Email reinhard.strametz@hs-rm.dePurpose: The objective of this study is to evaluate whether the nationwide establishment and institutionalization of a peer-support program, is economically justified given the potential positive effects on the Second Victim Phenomenon (SVP) among healthcare professionals in Germany.Methods: A comprehensive methodological approach was employed, using data from the SeViD studies to assess the prevalence and duration of SVP among physicians and nurses in Germany. Economic impact assessments were conducted to estimate the potential cost savings associated with implementing a peer-support program.Results: The economic analysis reveals significant annual costs associated with SVP-induced absenteeism: approximately 1.56 billion euros for physicians and 1.87 billion euros for nurses. Implementing comprehensive peer-support programs could reduce these costs to approximately 0.85 billion (physicians) and 1.02 billion euros (nurses), respectively, demonstrating substantial potential economic benefits.Conclusion: Investing in a structured peer-support program could yield annual savings exceeding 1.55 billion euros while enhancing workforce resilience and improving patient care. This underscores the economic rationale for scaling up peer support initiatives in healthcare settings.Keywords: peer support program, economic impact, second victim phenomenon, healthcare professionals